2011
DOI: 10.2474/trol.6.36
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cavitation Ring Formed on Laser-Textured Surface of Mechanical Seal

Abstract: It is considered that cavitation plays an important role in maintaining the sealing performance of mechanical seals. However, there are not any studies that demonstrated how to control cavitation regions and take advantage of them to improve the sealing performance of mechanical seals. In this study, we have tried to demonstrate that the cavitation rings could be formed and maintained by taking advantage of the laser-textured surface. Furthermore, the effects of the cavitation rings on the frictional character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…2 The concept of the present mechanism was found in previous studies, [33][34][35] which changed the surface profile of the pad but wholly different from those suggested in prior studies on textured surfaces. [3][4][5][6][7][8][10][11][12][13][14][18][19][20][21][22][23][24][25][26][27][28][29] Figure 13 shows the pressure distributions among the three conditions to understand the mechanism of the balancing wedge action when it promotes lubrication performance. The first case is a pivoted flat pad bearing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The concept of the present mechanism was found in previous studies, [33][34][35] which changed the surface profile of the pad but wholly different from those suggested in prior studies on textured surfaces. [3][4][5][6][7][8][10][11][12][13][14][18][19][20][21][22][23][24][25][26][27][28][29] Figure 13 shows the pressure distributions among the three conditions to understand the mechanism of the balancing wedge action when it promotes lubrication performance. The first case is a pivoted flat pad bearing.…”
Section: Discussionmentioning
confidence: 99%
“…Qiu and Khonsari 22 showed that steel ring specimens with textured dimples caused cavitation within the dimples to provide lower friction coefficients than flat specimens, whereas the wear of the textured specimens was greater than that of the flat specimens. Tokunaga et al 23 demonstrated ''cavitation rings'' in mechanical face seals, on which dimple-patterned lines were created in the circumferential direction, with lower friction compared to a flat specimen. Zhang and Meng 24 compared the cavitation zone in textured features on the basis of the JFO model with experimental observations.…”
Section: Introductionmentioning
confidence: 99%
“…Applying dimples and/or grooves to the lubricating area is an effective method for improving lubrication performance [1]. Consequently, this technology is being used in various mechanical elements such as bearings [2][3][4][5], seals [6][7][8], and piston rings [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…However, under the high parameter conditions, cavitation occurs easily between the friction pair (Payvar and Salant, 1992;Li et al, 2016). Compared to the pure liquid film lubrication, the serious cavitation changes the lubrication state of friction pair and further affects the sealing performances such as the loadcarrying capacity, friction characteristics and leakage (Tokunaga et al, 2011;Gropper et al, 2016;. So the cavitation phenomenon can't be ignored in the theoretical analysis and structural optimization design of hydrodynamic lubrication of texture surface including the SG-LFS.…”
Section: Introductionmentioning
confidence: 99%